PENDAMPINGAN USAHA GIPANG SINGKONG DALAM MENINGKATKAN PEMASARAN DI ERA PANDEMI COVID-19 - Ratu Sifa Ni’mah; Intan Permatasari; Nurul Hikmah; Puput Lestari; Ajeng Afifah Muhartini (Yayasan Education and Social Center, 2021)
The purpose of the Student Work Lecture Community Service Program is to increase the village potential and marketing of Gipang Dangdeur (cassava) in Kramatlaban village. The making of gipang is the object of this dedication. By using SWOT analysis, several problems were found as a result of internal weaknesses and external threats. The method of implementing this service is by using the Participation Action Research (PAR) method where the implementation is carried out through a participatory approach method, the implemented into an action, survey through observation, interviews, and analysis of village problems and potentials. Limited production, traditional manufacturing process and competition from Gipang produced by other regions. With this activity, the MSME group has product labels and marketing strategies using social media such as Instagram, Shopee, Facebook, WhatsApp which are carried out through digital technology. Directly through digital technology, it is able to increase and develop the selling value of cassava gipang craftsmen so that products can increase during the Covid-19 period. Several suggestions and proposals were generated, eith the hope that after implementation they would increase the marketing and selling value of the Gipang products, thereby increasing the welfare of the makers in particular and the people of the entire Kramatlaban village in general